Effects of Hatching Eggs Storage at Room Temperature on Hatching Performance and Day Old Chick Quality of Arab Chickens - Andri, Faizal; Fajriah, Putri; Tasya, Silvi Annas; Marwi, Filoza; Nurwahyuni, Eka; Yulianti, Dyah Lestari; Prayogi, Heni Setyo; Sudjarwo, Edhy (TERNAK TROPIKA Journal of Tropical Animal Production, 2024)
This study evaluated the effect of hatching egg storage at room temperature on hatching performance and day old chick quality of Arab chickens. Two hundreds hatching eggs were obtained at the same day from 55-weeks-old Arab chicken flocks. Hatching eggs were then randomly distributed into four treatments, including 1 day storage (1DS), 4 days storage (4DS), 7 days storage (7DS), and 10 days storage (10DS). Each of those treatment using five replicates and each of replicate consisted of 10 hatching eggs. Temperature and relative humidity in the storage room were 27.9 ± 0.55 °C and 55.4 ± 4.84%, respectively. At the end of each storage duration, hatching eggs were incubated at temperature and relative humidity of 37.8 ± 0.08 °C and 58.94 ± 5.66%, respectively, for 516 hours. Result showed that egg storage duration for up to 10 days did not affect (P > 0.05) fertility. However, 4DS treatment had a higher (P < 0.05) hatchability of set eggs and hatchability of fertile eggs. Embryonic mortality was also lower (P < 0.05) in 4DS than the other treatments. Egg storage duration had no effect (P > 0.05) on chick length, hatch yield, and Pasgar score. Whereas, chick weight in 1DS and D4S was higher (P < 0.05) than 7DS and 10DS. Furthermore, saleable chicks in 4DS also higher (P < 0.05) than the other treatments. It could be concluded that hatching egg storage at room temperature for 4 days provides optimum hatching performance and day old chick quality of Arab chickens.